Eflapegrastim versus Pegfilgrastim for Chemotherapy-Induced Neutropenia in Korean and Asian Patients with Early Breast Cancer: Results from the Two Phase III ADVANCE and RECOVER Studies - Moon, Yong Wha; Kim, Seung Ki; Lee, Keun Seok; Lee, Moon Hee; Park, Yeon Hee; Park, Kyong Hwa; Kim, Gun Min; Lim, Seungtaek; Lee, Seung Ah; Choi, Jae Duk; Baek, Eunhye; Han, Hyesun; et al. (Cancer research and treatment, 2023)
Purpose We investigated the consistent efficacy and safety of eflapegrastim, a novel long-acting granulocyte-colony stimulating factor (G-CSF), in Koreans and Asians compared with the pooled population of two global phase 3 trials.Materials and Methods Two phase 3 trials (ADVANCE and RECOVER) evaluated the efficacy and safety of fixed-dose eflapegrastim (13.2 mg/0.6 mL [3.6 mg G-CSF equivalent]) compared to pegfilgrastim (6 mg based on G-CSF) in breast cancer patients who received neoadjuvant or adjuvant docetaxel/cyclophosphamide. The primary objective was to demonstrate non-inferiority of eflapegrastim compared to pegfilgrastim in mean duration of severe neutropenia (DSN) in cycle 1, in Korean and Asian subpopulations.Results Among a total of 643 patients randomized to eflapegrastim (n=314) or pegfilgrastim (n=329), 54 Asians (29 to eflapegrastim and 25 to pegfilgrastim) including 28 Koreans (14 to both eflapegrastim and pegfilgrastim) were enrolled. The primary endpoint, DSN in cycle 1 in the eflapegrastim arm was non-inferior to the pegfilgrastim arm in Koreans and Asians. The DSN difference between the eflapegrastim and pegfilgrastim arms was consistent across populations: –0.120 days (95% confidence interval [CI], –0.227 to –0.016), –0.288 (95% CI, –0.714 to 0.143), and –0.267 (95% CI, –0.697 to 0.110) for pooled population, Koreans and Asians, respectively. There were few treatment-related adverse events that caused discontinuation of eflapegrastim (1.9%) or pegfilgrastim (1.5%) in total and no notable trends or differences across patient populations.Conclusion This study may suggest that eflapegrastim showed non-inferior efficacy and similar safety compared to pegfilgrastim in Koreans and Asians, consistently with those of pooled population.